2016
DOI: 10.1177/0731684416680456
|View full text |Cite
|
Sign up to set email alerts
|

Process modeling and parameter optimization based on assumed inherent sensor inversion for composite automated placement

Abstract: Composite automated placement shows great potential for efficient manufacturing of large composite structures. In order to realize online layup quality detection and parameter optimization with high speed and desired layup quality, a methodology is developed based on assumed inherent sensor inversion. First, it is necessary to conduct sensitive analysis in order to analyze the importance of process parameters and their changes. Then the relationship between these process parameters and the layup quality could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…And calculate pressure distribution along the whole path in Loop 3. Since each mesh will undergo a pressure rise from zero to maximum and back down to zero in AFP process, the average pressure of each mesh is taken as the pressure along the whole path, as shown in equation (10).…”
Section: Case Of Calculating Pressure Distribution Under Segmented Ro...mentioning
confidence: 99%
See 1 more Smart Citation
“…And calculate pressure distribution along the whole path in Loop 3. Since each mesh will undergo a pressure rise from zero to maximum and back down to zero in AFP process, the average pressure of each mesh is taken as the pressure along the whole path, as shown in equation (10).…”
Section: Case Of Calculating Pressure Distribution Under Segmented Ro...mentioning
confidence: 99%
“…4,5 Compaction force is one of the most important process parameters for AFP, and many studies have shown that appropriate compaction force helps to improve prepreg tack levels and layup quality. [6][7][8][9][10][11] However, little attention has been paid to the compaction pressure (the force per unit area on prepreg layers, unit: Pa), which is more essential than compaction force (unit: N). At present, most of the researches on AFP process were carried out on flat mold, in which case the compaction pressure distribution is relatively even.…”
Section: Introductionmentioning
confidence: 99%
“…The process temperature, speed, compaction pressure [1][2][3][4][5], fiber path planning [6][7][8][9], and processinduced defects [10][11][12] are the important factors for developing a proper bonding quality at the interface between the tape and substrate to manufacture products with high mechanical performance. In addition, optimal ranges of the tape winding and placement parameters such as tape tension and roller force are necessary to reduce the void content [13,14] and residual stress [15,16] and to increase the tensile strength [13,15], interlaminar shear strength [17,18], peel strength [19,20], and production rate [16,18,19] The nip point temperature serves as an indicator for the process temperature and might vary during the LATW process, possibly resulting in a substantial variation in the consolidation quality. For instance, the nip point temperature increases significantly with the increase of substrate thickness during the continuous multi-layer hoop winding process due to heat accumulation in previously wound layers [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Qing Yu Cui et al [ 14 ] analyzed the function of tension by measuring the physical and mechanical properties of specimens, and considered that the wrinkles and waves on the surface of the T300/epoxy bearing composites can be eliminated using the proper method. The importance of tape placement process parameters was discussed, initially, in Jinxiang Cheng’s article [ 15 ]. Subsequently, a genetic algorithm combined with multi-objective optimization theory was applied to determine an optimum set of factors for obtaining the desired composite components with high speed and best layup quality.…”
Section: Introductionmentioning
confidence: 99%